Metal‐Organic Framework‐Based Nanoheater with Photo‐Triggered Cascade Effects for On‐Demand Suppression of Cellular Thermoresistance and Synergistic Cancer Therapy. Issue 13 (31st March 2022) - Zhu, Yuanyuan; Huang, Yanyan; Yan, Tian‐Hao; Li, Jialuo; Li, Yongming; Drake, Hannah F.; Zhong, Huifei; Jin, Yulong; Zhao, Rui; Zhou, Hong‐Cai
Abstract: Nanomedicine with stable light‐heat conversion and spatiotemporally controllable drug activation is crucial for the success of photothermal therapy (PTT). Herein, a metal–organic framework (MOF)‐based nanoheater with light‐triggered multi‐responsiveness is engineered to in‐situ and on‐demand sensitize cancer cells to local hyperthermia. Well‐dispersed platinum nanoparticles synthesized inside nanospaces of the MOF are employed as the near‐infrared (NIR)‐harvesting unit with stable and high light–heat conversion performance. A conformation switchable polymer shell is constructed as a secondary light‐responding unit to gate the targeted activation of a molecular inhibitor against thermoresistance. By cascade transformation of light stimuli to downstream signals, the nanoheater enables inhibitor release to go with local heating at the same time restricted in lesion sites to maximize efficacy and minimize systemic toxicity. The efficient photothermal conversion and the blockage of cellular heat‐protective pathways provide a dual‐mode of action which selectively sensitizes cancer cells to hyperthermia in a spatiotemporally controlled manner. With NIR as the remote switch, the MOF‐based nanosystem demonstrates localized and boosted PTT efficacy against cancer both in vitro and in vivo. These results present nanosized MOFs as tailorable and versatile platforms for synergistic and precise cancer therapy. Abstract : A metal–organic framework‐based nanocomposite is engineered to sequentially transduce near infrared irradiation to heat, polymer conformation transition, and drug release. With light as the remote switch, blockage of cellular heat‐protective pathway can be achieved to match the time window and spatial distribution of heating, which significantly sensitizes cancer cells to hyperthermia with minimal systemic toxicity in vitro and in vivo.